Preparation of spiramycin fermentation residue derived biochar for effective adsorption of spiramycin from wastewater. (June 2022) - Gao, Tong; Shi, Wansheng; Zhao, Mingxing; Huang, Zhenxing; Liu, Xiaoling; Ruan, Wenquan
Abstract: Spiramycin (SPI) fermentation residue (SFR) is classified as hazardous waste in China because of the residual antibiotics in it. SFR disposal in the traditional way is costly and wasteful of resources. In this study, pyrolysis method was adopted to covert SFR to biochar for SPI removal from wastewater, and the SPI adsorption performance was investigated. The results showed that the optimal pyrolysis temperature was 700 °C as the prepared biochar BC700 exhibited the highest SPI removal efficiency. The specific surface area of BC700 was 451.68 m 2 /g, and the maximum adsorption capacity was 147.28 mg/g. The adsorption mechanism involved electrostatic interaction, pore filling, π-π interaction, hydrogen bonding, and the participation of C–C and O–CO functional groups in the adsorption. No residual SPI was detected in BC700 indicating the detoxification of SFR was achieved. Moreover, after recycling for 5 times, the SPI removal efficiency was still higher than 80.0%. Therefore, this study could provide a promising method for SFR disposal. Graphical abstract: Image 1 Highlights: Spiramycin fermentation residue (SFR) detoxification attained by pyrolysis. The biochar prepared under 700 °C was the best for SPI removal. 100% of SPI can be removed from wastewater when the BC700 dosage was 2.0 g/L. The maximum SPI adsorption capacity of BC700 was 147.28 mg/g. After being recycled for 5 times, SPI removal rate was still higher than 80.0%.